2017
DOI: 10.3389/fneur.2017.00190
|View full text |Cite
|
Sign up to set email alerts
|

Eyelid Retraction in Isolated Unilateral Congenital Blepharoptosis

Abstract: Isolated unilateral congenital ptosis is encountered relatively infrequently in clinical practice. It typically consists of a unilateral droopy eyelid, weak levator palpebrae superioris muscle function, lid lag, and an absent upper lid crease with no other abnormalities on examination. We present a four-and-a-half-year-old girl with isolated and mild unilateral congenital ptosis who unexpectedly demonstrated a static upper eyelid on downgaze in conjunction with a well-formed upper lid skin crease. We attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The condition presents as a stiff ptosis eyelid with poor contraction function and incomplete relaxation, identical to lid lag. Furthermore, similar to Marcus Gunn jaw-winking syndrome, synkinesis with ptosis is a rare condition with an association between abnormal innervation of the levator palpebrae superioris muscle and the impaired movement of the mouth or jaws; this condition is similar to that reported in this case [4]. Although the surgical process for ptosis has advanced and further improved, the surgical methods for monocular congenital ptosis with synkinesis or impaired innervation vary and remain controversial; this is mostly because of lagophthalmos after surgery.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…The condition presents as a stiff ptosis eyelid with poor contraction function and incomplete relaxation, identical to lid lag. Furthermore, similar to Marcus Gunn jaw-winking syndrome, synkinesis with ptosis is a rare condition with an association between abnormal innervation of the levator palpebrae superioris muscle and the impaired movement of the mouth or jaws; this condition is similar to that reported in this case [4]. Although the surgical process for ptosis has advanced and further improved, the surgical methods for monocular congenital ptosis with synkinesis or impaired innervation vary and remain controversial; this is mostly because of lagophthalmos after surgery.…”
Section: Introductionsupporting
confidence: 81%
“…Recent findings suggest that congenital ptosis is probably secondary to impaired innervation of the levator palpebrae muscle [4]. A case report on an infant with congenital blepharoptosis retraction of the right eyelid supported the phenomenon of ptosis with impaired innervation.…”
Section: Discussionmentioning
confidence: 83%
“…The classic presentation is a non-progressive ptosis that is unilateral in 75% of cases and asymmetric when bilateral [17] . Recent histopathological studies of isolated congenital myogenic ptosis have shown a dysgenesis of the anterior portion of the levator palpebrae superioris with striated muscle fiber loss and loose connective tissue proliferation, which impairs the ability of the levator to contract or relax [18][19][20] . Examination findings are reflective of the histopathology where levator function is markedly decreased, and the upper eyelid crease is poorly formed or absent in severe cases.…”
Section: Myogenic Ptosismentioning
confidence: 99%
“…Ptosis refers to the improper position of the upper eyelid edge relative to the upper corneoscleral rim not due to reasons such as poor eyesight and blepharoptosis. Such a situation in a child at birth or in the first year after birth can be diagnosed as congenital ptosis, and unilateral ptosis accounts for 64.7-75.0% of all types of ptosis ( 1-3 ). Congenital ptosis can be classified into mild, moderate, or severe ptosis ( 4 ), which is mainly caused by the following reasons: The upper eyelid cannot lift or is in partial or complete ptosis due to hypoplasia of levator muscle, defects of Müller smooth muscle, or nerve defects of upper eyelid muscle ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%